E-Booklet as Communication Strategy to Influence Change on Tourist’s Behaviour in Bali - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2023)
Tourist’s demand led to an increasingly complex travel trend. as a result, numerous competitors rising to Indonesia tourism sector with various innovations and patterns of tourism communication. E-booklet is one of many products to build the image of quality tourism and Green Tourism in Indonesia. As a promotional medium, the e-booklet became a marketing communication strategy carried out by the Ministry of Tourism and creative arts in collaboration with the private sector since 2018. Together with the Grab Indonesia company, the Ministry of Tourism launched 2 types of e-booklets about Bali tourist destinations in mid-2022 and early 2023. In its implementation, two e-booklets entitled Bali Magz: Eat, explore, and Enjoy Bali and Exploration of the Enchantment of the Island of the Gods have provided comprehensive, visually interesting, and informative information. The nature of the e-booklet, which contains promotions and suggestions, is contained and can help tourists to choose the desired destination. These two e-booklets have been uploaded to the official website of the Ministry of Tourism and Creative Economy. Socialization from the government, ease of access to e-booklets, and understanding of tourists are indicators of the success of booklets in educating tourists. In the future, booklets would be perfected as promotional media to fulfil various elements of booklets and e-booklets. Planning for the preparation of the e-booklet is also needed so that each thing tourists need to know can be accommodated in the next guidebook. In the future, Indonesian Tourism, in general, and Bali, in particular, can achieve maximum success.